(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate breastfeeding in the first month of life in term and preterm babies after hospital discharge, assisted by a maternal and child dental care program, through the parameters of the Tavares protocol (2008). This is a cross-sectional observational study, whose sample is composed of babies assisted in an extension project at the Federal University of Piauí. The study was approved by the Ethics Committee of the Federal University of Piauí UFPI (opinion 1381135). Data collection was performed by a single author, an undergraduate student in Dentistry. For the application of the questionnaire and observation of the breastfeeding, there was a previous training that configures a pilot study using the questionnaire with 10 pairs. Newborns who went to the maternal and child care program from August 2015 to May 2016 were evaluated, according to the parameters present in the questionnaire proposed by Tavares 2008. A total of 103 babies, pre - term (PT) to term (AT), of these, 96 babies of both sexes participated in the study. Seven babies were excluded for not remaining awake and responsive during observation. Premature and low birth weight babies present greater difficulties and more indicative signs of a problem at the time of breastfeeding, when compared to full-term babies, even after hospital discharge, hence the need for better monitoring by the health team. after hospital discharge.